Synthesis and coupling reactions of alpha,alpha-dialkylated amino acids with nucleobase side chains. - Azumaya, I (1995)
Several di- and tripeptides containing protected purine (adenine) and pyrimidine (thymine) residues on their side chains were synthesized. The parent amino acids alpha, alpha-dialkylated in a symmetrical manner. An effective coupling procedure was developed for these sterically hindered amino acids: the fluoren-9-ylmethyloxycarbonyl-protected amino acid was dehydrated to its oxazolinone form, which was coupled in good yields with amino esters in hot tetrachloroethane.